STUDI DAMPAK PEMBERDAYAAN SISTEM KEUANGAN SYARIAH AL-IJARAH BAGI PELAKU UMKM - Khasanah, Umrotul; Meldona, Meldona; Djakfar, Muhammad (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Al-Ijarah's Islamic Financial System has produced strategic results. The Islamic financial system to differentiate from conventional financial systems based on interest (interest), the Islamic financial instrument is the al-ijarah (lease) system. This study aims to reveal the impact of Micro, Small, and Medium Enterprises (MSME) business actors on the Islamic financial system using the al-ijarah instrument; reveal the effect of business land managers leased to MSMEs regarding the Islamic financial system using the al-ijarah instrument. This research puts forward a qualitative descriptive research method with case studies of culinary business actors and providers of land for rent in Malang Raya, East Java. Data analysis uses a gradual approach, namely: analyzing important statements, formulating, describing, reducing data towards findings, propositions, and conclusions. The researcher, as the main instrument, performs data analysis simultaneously. Researchers prioritize observation and interviews. This research found two things: (1) Al-Ijarah business actors successfully overcame obstacles and obstacles. However, they initially applied their abilities as they were, but they could use their management skills quite well after developing. (2) The benefits for entrepreneurs who provide business / al-ijarah land leases are that they are successful in delivering strategic places, easy to reach, availability of parking spaces, and security aspects.